2008
DOI: 10.1080/00016480801901659
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of quantitative analysis of facial nerve enhancement on MRI in Bell's palsy

Abstract: The lesion side showed significantly higher signal intensity increase compared with the normal side in all of the segments except for the mastoid segment. Signal intensity increase at the internal auditory canal and labyrinthine segments showed correlation with the initial degree of facial palsy but no significant difference was found between different prognostic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 17 publications
0
20
0
Order By: Relevance
“…This normal enhancement of the facial nerve often hinders the clinical use of conventional MR imaging in clinical practice both for diagnostic purposes and for predicting outcomes despite its high sensitivity. 7,[24][25][26] Our results showed that the CE 3D-FLAIR sequence has an advantage in evaluating the pathologic enhancement of the facial nerve over the 3D-T1-FFE sequence, with higher specificity. The results from our study are likely due to the characteristics of the FLAIR sequence.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This normal enhancement of the facial nerve often hinders the clinical use of conventional MR imaging in clinical practice both for diagnostic purposes and for predicting outcomes despite its high sensitivity. 7,[24][25][26] Our results showed that the CE 3D-FLAIR sequence has an advantage in evaluating the pathologic enhancement of the facial nerve over the 3D-T1-FFE sequence, with higher specificity. The results from our study are likely due to the characteristics of the FLAIR sequence.…”
Section: Discussionmentioning
confidence: 99%
“…However, the major disadvantage of EPS is its inability to detect diagnostic abnormalies of the nerve distal to the stylomastoid foramen within 1 week of symptom onset. 1 Although the potential of MR imaging has been studied as part of the effort to find other helpful diagnostic techniques over the past 20 years, [2][3][4][5][6][7][8][9][10] its results have been largely disappointing. Gd-DTPA-enhanced T1-weighted spin-echo and 3D spoiled gradient-echo sequences have shown significant limitations in diagnosing and predicting outcomes in patients with facial neuritis; the geniculate ganglion, tympanic, or mastoid segment of the normal facial nerve can be significantly enhanced in up to 76% of patients due to the distribution of arteriovenous plexus along the facial nerve, which, in turn, may inhibit evaluation of the pathologic enhancement of the nerves resulting from breakdown of the blood nerve barrier.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many of these tests are of questionable benefit in Bell's palsy, including laboratory testing, 9,10 diagnostic imaging studies, and electrodiagnostic tests. [10][11][12] Furthermore, while patients with Bell's palsy enter the health care system with facial paresis/paralysis as a primary complaint, not all patients with facial paresis/paralysis have Bell's palsy. It is a concern that patients with alternative underlying etiologies may be misdiagnosed or have unnecessary delay in diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Although the diagnostic utility of MRI in patients with facial neuritis has been studied over the past 20 years, its results have been largely disappointing (1)(2)(3)(4)(5). …”
mentioning
confidence: 99%